Quality of Well Waters of Jaipur District - Paliwal, K V; Gandhi, A P (Annals of Arid Zone, 2016)
Chemical analysis of 92 representative well waters of ChaksuPanchayat Samiti of Jaipur District was carried out to evaluatetheir quality for irrigation purposes. In general, thewaters are highly saline and are of Na-Mg-Ca and Cl-Cos+RCO3-SO4, type. About 95 per cent samples have more Mgthan Ca. Bicarbonate rich waters are low in Ec while Cland Na are the dominant ions in highly saline waters. It isproposed that ratios of cations and anions should also beexpressed while evaluating the quality of irrigation water.